Is Fintech a Friend or Foe? Mediating Effects in the Journey from Literacy to Financial Behavior - Suryanto, Angelina; Radianto , Wirawan E. D.; Nahar, Faiza Husnayeni (Universitas Brawijaya, Indonesia, 2025)
This study examines the influence of financial literacy and socialization on financial management behavior, with the perceived usefulness of financial technology as a mediating variable. The increasing use of digital financial services among students has raised questions about whether fintech truly enhances financial management or instead fosters impulsive financial habits. A quantitative research design was applied using a conclusive causal approach. Primary data were collected via online questionnaires distributed to students from six public and private universities in Surabaya, Indonesia. Using purposive sampling, 705 valid responses were obtained from students aged 19–22, currently in semesters 2 to 6, and users of financial technology services such as mobile banking, e-wallets, and investment platforms. Data analysis was conducted using PLS-SEM. The findings show that financial literacy and socialization positively and significantly influence financial management behavior. However, the perceived usefulness of financial technology has a negative effect on financial management behavior. Furthermore, perceived usefulness of financial technology partially mediates the relationship between financial literacy and financial behavior, but does not mediate the relationship between financial socialization and financial behavior. This study contributes novel insights by highlighting the asymmetric mediating role of fintech, challenging the common assumption that technology constantly improves financial outcomes. The results imply the need for educational institutions to enhance students’ digital financial literacy and promote critical awareness of how fintech features may encourage excessive consumption despite good financial knowledge.